Time interval from transurethral resection of bladder tumour to bacille Calmette–Guérin induction does not impact therapeutic response. (5th May 2021) - Hensley, Patrick J.; Bree, Kelly K.; Brooks, Nathan; Matulay, Justin; Li, Roger; Nogueras González, Graciela M.; Navai, Neema; Grossman, Herbert B.; Dinney, Colin P.; Kamat, Ashish M.
Abstract : Objectives: To investigate bacille Calmette–Guérin (BCG) tolerability and response with respect to the timing of BCG administration after transurethral resection of bladder tumour (TURBT) in patients with non‐muscle‐invasive bladder cancer (NMIBC). Patients and Methods: A review of patients with NMIBC at our institution managed with at least 'adequate BCG' (defined by the United States Food and Drug Administration as at least five of six induction instillations, with two additional instillations comprising either maintenance or repeat induction) at our institution from 2000 to 2018 was performed. Time from TURBT to first instillation of induction BCG was stratified by quartile and analysed as a continuous variable. Kaplan–Meier and log‐rank tests analysed differences in recurrence‐free (RFS) and progression‐free survival (PFS). Cox proportional hazards regression models identified associations between risk factors and survival outcomes. Results: A total of 518 patients received adequate BCG at a median (range) of 26 (6–188) days from TURBT. Overall, 45 patients (9%) developed BCG intolerance at a median (range) 12 (7‐33) instillations. When time from TURBT to BCG was stratified into quartiles, there was no difference with respect BCG intolerance ( P  = 0.966), RFS ( P  = 0.632) or PFS ( P = 0.789). On both uni‐ and multivariate regression analysis for RFS and PFS, time from TURBT to BCG was not a significant predictor when analysed by quartile or as a continuous variable (the hazard ratio for RFS was 1.00, 95% confidence interval [CI] 0.99–1.00, P  = 0.449; and for PFS was 0.99, 95% CI 0.98–1.00, P  = 0.074). Conclusion: The rates of tolerability and response to adequate BCG are not predicated by the timing of induction BCG instillation after TURBT. Early administration in properly selected patients is safe and delays do not affect therapeutic response.